Access to continuing education : a clientele analysis of the Hawkes Bay Community College : a thesis for the degree of Master of Education at Massey University - Benseman, John (Massey University, 1979)
Access to Continuing Education is largely confined to a small section of the adult population. Clientele analysis of Continuing Education institutions throughout the world have shown participants in Continuing Education to be consistently similar in terms of their social and demographic characteristics. Most participants are already advantaged in terms of their life-style - a narrow 'creme de la creme' sector of the population. Few Continuing Education institutions have set out to cater for the educational needs of all persons in an area - including the disadvantaged. This thesis presents the findings of a clientele survey of the Hawkes Bay Community College. From the beginning, College administrators were committed to catering for all groups within the Hawkes Bay population. This study analyses the characteristics of all persons attending College programmes in September 1978 and assesses their representativeness of the region's population. In brief, it describes the social and demographic characteristics of persons for whom the College provided access to Continuing Education. A self-administering questionnaire was completed by 1849 College clients and the results were compiled using the Statistical Package for the Social Sciences on a Burroughs 6700. Questionnaire items covered the respondent's age, sex, ethnicity, marital status, place of residence, occupation, income, present and past education. Analysis of the participants in terms of these factors shows that the College has succeeded in attracting a number of persons from groups which have previously been under-represented in Continuing Education. Increased rates of participation are found among members of ethnic minorities, persons with low-status occupations and persons with low levels of educational attainment and consumption. Within the College itself, the Community Education department attracts a more heterogeneous clientele than the Vocational Education department. Much of the latter group's homogeneity stems from its youthful age structure. Most prominent among non participants at the College are older men, older members of ethnic minorities, semi - and unskilled workers and residents of small towns and rural areas. Although the College has been successful in attracting numbers of people from groups not usually involved in Continuing Education, these groups are still under-represented at the College on a proportional basis. The College clientele is still dominated overall by groups who have always had high participation rates in Continuing Education. The Hawkes Bay Community College has, however, been successful in making headway towards opening up access to Continuing Education for all groups, including the disadvantaged.
Keywords: Hawke's Bay Community College (N.Z.); Adult education -- New Zealand -- Hawke's Bay